Blasphemy and Defamation of Religions in a Polarized World: How Religious Fundamentalism Is Challenging Fundamental Human Rights - Gubo, Darara Timotewos (Lexington Books, 2014)
The twenty-first century has been significantly shaped by the growing importance of religion in international politics resulting in rising polarization among nation states. This new dynamic has presented new challenges to international human rights principles. This book deals with some of these new challenges, particularly the growing demand by Muslim states for protection of Islamic religion from blasphemy and defamation. Member states of the Organization of Islamic Cooperation (OIC), through resolutions at the United Nations, made efforts to introduce laws that globally protect Islamic religion from blasphemy and defamation. The bid by OIC member states faced opposition from Western countries. The conflicting claims of the two sides are discussed in this book. The book clearly shows the impact of blasphemy and defamation of religion laws on certain aspects of fundamental human rights principles.